Analysis of Nurse Care Behavior and Patient Satisfaction in X Hospital - Sipayung, Putri Labibah Asrianto; Shaluhiyah, Zahroh; Dwiantoro , Luky (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The service that most affects patient satisfaction is nursing services. Whether or not patients are satisfied with health services is an indicator and one of the determining factors for the good and bad quality of professional nursing care. For this reason, this study aims to analyze nurses' caring behavior and patient satisfaction at the X Hospital. This type of research is quantitative with a cross sectional approach. The sample selection technique used purposive sampling and calculations were carried out using the slovin formula so that a sample of 119 patient respondents was found, both BPJS patients and general patients. Data collection was carried out in October-December 2022. The analysis used in this study included the chi square test, as well as multivariate analysis using ANOVA. The processing of this research data uses the help of SPSS software. The results showed that the patient age was a variable that was not related to the Principles of Nursing Care Caring Behavior, Leadership and Management of Caring Behavior, and Inpatient Satisfaction of X Hospital. While the variables related to the Principles of Nursing Care Caring Behavior, Leadership and Management of Nursing Care Caring Behavior, and Inpatient Satisfaction of X Hospital are variables of patient gender, patient education level, patient payment type is expected that there will be an increase in Caring leadership attitude between nurses to improve a good work environment between nurses. For hospitals, management improvement is needed to evaluate the provision of health services to BPJS patients and general patients.